2009
DOI: 10.1056/nejmoa0904267
|View full text |Cite|
|
Sign up to set email alerts
|

Asymptomatic Reactivation of JC Virus in Patients Treated with Natalizumab

Abstract: Background Progressive multifocal leukoencephalopathy (PML) occurs in a fraction of patients with multiple sclerosis who were treated with natalizumab. Most adults who are infected with the JC virus, the etiologic agent in PML, do not have symptoms. We sought to determine whether exposure to natalizumab causes subclinical reactivation and neurotropic transformation of JC virus. Methods We followed 19 consecutive patients with multiple sclerosis who were treated with natalizumab over an 18-month period, perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
6
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(143 citation statements)
references
References 29 publications
8
125
6
4
Order By: Relevance
“…16 A second putative mechanism is that natalizumab could promote mobilisation of peripheral-blood mononuclear cells from the bone marrow, some of which may harbour latest JCV infection. [17][18][19] This study observed many "large increases" in prospective anti-JCV Ab index, disproportionate to the effect that would be expected from increasing age . 6 The mean increase in anti-JCV Ab index occurs regardless of baseline index, other than those with extreme high index (>3)..…”
Section: Outteryck Et Al (2014) Compared Longitudinal Serostatus In mentioning
confidence: 59%
“…16 A second putative mechanism is that natalizumab could promote mobilisation of peripheral-blood mononuclear cells from the bone marrow, some of which may harbour latest JCV infection. [17][18][19] This study observed many "large increases" in prospective anti-JCV Ab index, disproportionate to the effect that would be expected from increasing age . 6 The mean increase in anti-JCV Ab index occurs regardless of baseline index, other than those with extreme high index (>3)..…”
Section: Outteryck Et Al (2014) Compared Longitudinal Serostatus In mentioning
confidence: 59%
“…18 We cannot exclude the possibility that higher rituximab doses may be necessary to reduce proteinuria in resistant forms of INS. Moreover, it is important to emphasize that rituximab toxicity, including lung fibrosis 38 and progressive multifocal leukoencephalopathy, 39 could be a function of the number of infusions and cumulative dose. A program of virus monitoring in urine and blood cells of our patient cohort (e.g., JC virus, the etiologic agent of progressive multifocal leukoencephalopathy) for the next few years is in place.…”
Section: Discussionmentioning
confidence: 99%
“…Potential complications have been described, such as lung fibrosis (33) and progressive multifocal leukoencephalopathy (34). Virus monitoring (e.g., JC virus-the etiologic agent of progressive multifocal leukoencephalopathy) in urine and blood cells and data on B cell deprivation are essential requirements for a long-term follow-up program.…”
Section: Discussionmentioning
confidence: 99%